2021
DOI: 10.1186/s40561-021-00149-8
|View full text |Cite
|
Sign up to set email alerts
|

Learner-content interaction in e-learning- the moderating role of perceived harm of COVID-19 in assessing the satisfaction of learners

Abstract: Envisioning learning sans interaction is absurd. Interaction plays a pivotal role in the efficacy and effectiveness of the present-day blended learning systems. Learner-content interaction contributes predominately towards the successful realization of the expected learning outcomes. In order to satisfy the learners and to impart them quality knowledge and education, e-learning content comprising of excellent learning and website content is of paramount importance. In the present COVID-19 outbreak challenging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 39 publications
7
64
0
9
Order By: Relevance
“…This finding suggests that the course content provided in Edmodo improved students' understanding and autonomy in their learning (Ngo & Ngadiman, 2019). In support of our finding, Kumar, Saxena, and Baber (2021) surveyed 435 undergraduate and graduate management students and discovered that "both the learning content and website content provided under the online study environment are important factors of e-learning quality, having a positive effect on e-learning quality and student satisfaction" (p. 11). Gopal, Singh, and Anggarwal (2021) discovered that the design of the course content is an important factor influencing student satisfaction in a survey of 544 M.B.A students in India.…”
Section: Interaction Student-content Interactionsupporting
confidence: 63%
See 1 more Smart Citation
“…This finding suggests that the course content provided in Edmodo improved students' understanding and autonomy in their learning (Ngo & Ngadiman, 2019). In support of our finding, Kumar, Saxena, and Baber (2021) surveyed 435 undergraduate and graduate management students and discovered that "both the learning content and website content provided under the online study environment are important factors of e-learning quality, having a positive effect on e-learning quality and student satisfaction" (p. 11). Gopal, Singh, and Anggarwal (2021) discovered that the design of the course content is an important factor influencing student satisfaction in a survey of 544 M.B.A students in India.…”
Section: Interaction Student-content Interactionsupporting
confidence: 63%
“…These findings have some implications for the body of knowledge in the field of student satisfaction, where the emphasis must be placed on incorporating various types of interaction into Web-based learning processes during the COVID-19 pandemic. Course content that can help students learn during the pandemic is essential (Kumar et al, 2021;Gopal et al, 2021). The presence of a teacher during online learning has a significant impact on student satisfaction (Suryani & Sugianingrat, 2021;Foerderer et al, 2021;Gray & DiLoreto, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Chinese online education advocates "interactivity" in online learning provides some perspectives to access online learning in our study. As students' satisfaction reflects the effectiveness of e-Learning quality (Alqurashi, 2019), it has become very important to understand how interactions impact the e-Learning quality, especially during the pandemic when the education around the world has moved to online teaching & learning (Kumar et al, 2021). However, the literature is not exhaustive on student satisfaction in an online environment during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Student-teacher interaction aims to increase students' knowledge through dialogues between the student and the teacher and is essential when considering how to enhance students' learning outcomes and perceived satisfaction (Anderson, 2008;Çardak & Selvi, 2016;Kumar et al, 2021). Park (2015) found that a lack of facilitation can influence the quality of the learning process, and that students might perceive themselves as isolated, which may affect their interactivity level.…”
Section: Interaction Theory In Blended Learningmentioning
confidence: 99%